EFFECT OF KAP SUBSTITUTION AND ANNUAL REPORT DISCLOSURE ON MARKET REACTIONS - Nita Nurul Fajar; Listiya Ike Purnomo (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2019)
The purpose of this study is to find out how much the market reaction is influenced by the substitution of KAP and disclosure of annual reports in a given period. Abnormal Return is used as a measurement for market reactions while the variables used in this study are Substitution of KAP and mandatory disclosures used to measure disclosure of annual reports. The data use form of audited financial statements by an independent auditor obtained from the official IDX website www.IDX.com using a purposive sampling method based on certain criteria. Samples in this study were 16 manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. So that the total sample obtained is 80 company data. Hypothesis testing is done by using multiple linear regression data analysis techniques. Data is collected, then processed and analyzed using the SPSS 22.0 for Windows application program. The results of this study are Substitution of KAP had a significant effect while the disclosure of the annual report had no effect, but the two variables simultaneously had an effect on the market reaction.